APPLICATION OF BUZZER & VIBRATION SENSOR FOR VEHICLE TRACKING SYSTEM INVOLVED DROWSINESS DETECTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the present era of computerization and robotics, the industries are very serious about the efficiency of processes and minimizing the losses. The competition in the business leads to make sturdy decisions concerning the process control. Several times it was observed that, during the repeated and continuous operations, workers have faced severe accidents due to sleepiness. In India around 400 deaths in road accidents occurs every day, significant amount of which is due to sleep. In most of the night transports the sleep of the driver is one of the severe causes for accidents. Authors are trying to provide the solution to this problem. In the implemented model the smart system for observing the human awaken condition is proposed. A system designed with display, GPS, GSM, vibrator, regulator and rectifier to act as support system to save human life.